Limonin enhances osteoblastogenesis and prevents ovariectomy-induced bone loss - Da-Hye Lee (Journal of Functional Foods, 2016)
Limonin, the most prevalent limonoid in citrus fruits, is widely used as a dietary supplement because of its biological activities. Although studies have shown that limonin inhibits bone resorption in osteoclasts and improves bone quality in orchidectomised rats, the anti-osteoporosis activity of limonin in ovariectomised (OVX) animal models is still unknown, and its exact molecular mechanisms remain undefined. Therefore, the effect of limonin on osteoblastogenesis in MC3T3-E1 cells and an OVX-induced osteoporosis rat model was investigated. Limonin stimulated alkaline phosphatase (ALP) activity, mineralisation, and increased osteoblast differentiation gene marker expression via extracellular signal-regulated kinase (ERK) and p38 signalling in osteoblastic MC3T3-E1 cells. In animals, limonin decreased OVX-induced body weight increase, affected the trabecular bone structure and biochemical properties, and facilitated bone mineral density and content regulation. These findings demonstrated that limonin has beneficial bone metabolism effects based on bone formation and might have potential as a functional food ingredients and a dietary supplement for osteoporosis.